A 3D interpolation method for base-station-antenna radiation patterns. - Gil, Francisco (IEEE Antennas & propagation magazine.)
A simple method for the estimation of three-dimensional radiation patterns from the horizontal and vertical cuts is presented, which leads to lower errors compared to some common methods. In order to evaluate its reliability, the method has been tested for various theoretical cases by considering dipoles, individually or in arrays. For the case of the half-wavelength dipole, a maximum error of 12.0 dB (for directions of very low radiation) and an average error of 1.6 dB were obtained; for a uniform array of two dipoles radiating in a half-plane (which leads to a similar GSM panel-antenna's radiation pattern), the average error was 1.8 dB (on the whole sphere). Measurements were also conducted in a real GSM network, and different approximations for the base-station radiation pattern were compared. The method presented here leads to a lower error, its average absolute value being 4.0 dB. This interpolation method is very useful for incorporating full three-dimensional radiation patterns into mobile-communications planning tools.